Selected factors affecting Malaysian palm oil export demand to China - Ahmad, Mohammad Yusof (2020)
Besides India and the European Union (EU), China is the major importer country for Malaysian palm oil. Among these countries, China has a tremendous demand performance for Malaysian palm oil, and it was named as the top largest importer country of Malaysian palm oil for twelve consecutive years from 2002 to 2013. However, in the year 2014, China had suddenly reduced its demand for Malaysian palm oil by almost 50% in just three years period despite constant growth in its economy and continuous depreciation of the Malaysian Ringgit. This situation has become a challenge for the Malaysian palm oil industry as the declining trend in demand by China is driven by its behavioural change of import from palm oil to soybean. It is also accompanied by a switch in China’s import preference for palm oil from Malaysia to Indonesia. This scenario had affected the Malaysian palm oil industry which plays an important role as one of the main contributors to the national income in terms of GDP. In fact, the decline in export demand will also affect the Malaysian palm oil industry economy where the competitiveness of Malaysian palm oil would deteriorate, and both the export revenue and farmer's income would decline. Thus, what are the significant factors that influence the demand for Malaysian palm oil export to China? Firstly, the result obtained from the ARDL Bounds test showed statistically significance at 5% level. This indicates that all the estimated regressors have a long run cointegration relationship with the China import demand for Malaysian palm oil. The long-run regression shows that only the export price of Indonesian palm oil is not significant to determine China’s palm oil import demand from Malaysia. However, the export price of Malaysian palm oil to China, global price of soybean oil and China real GDP per capita are significant at 5% significance level while the exchange rate of Malaysian Ringgit per Chinese Yuan is the only significant factor at 1% significance level in determining the export demand of Malaysian palm oil to China. Besides that, all the estimated variables were found to follow the prior expected sign where the export price of Indonesian palm oil, global price of soybean oil, exchange rate and China real GDP per capita each has a positive relationship while the export price of Malaysian palm oil to China has a negative relationship with the export demand to China. Furthermore, the estimated elasticities showed that Malaysia’s currency exchange rate is the most important factor to determine the demand in the long run since the variable of elasticity of exchange rate is statistically significant at 1% significance level. The elasticity was estimated at 2.809 which indicates that if the currency depreciates by 1%, it will cause the demand to increase by 2.809%, holding other factors constant. In the short run, all the estimated variables still follow the expected sign except for the export price of Malaysian palm oil lagged one year. However, China real GDP per capita turned out to be insignificant and the export price of Indonesian palm oil remained insignificant in determining the demand in the short run. In the nutshell, Malaysia’s exchange rate stability is the most important factor in determining its palm oil export demand to China in the long and short run. Therefore, the policymaker is encouraged to develop and formulate plans and strategies to minimise the impact of currency instability on the palm oil industry. In addition, the industry players are advised to be more efficient in managing the export price by regulating the export tax and implementing an efficient pricing strategy. Upgrading the products through research and development also beneficial to create a product differentiation. The export price of Indonesian palm oil was found to be insignificant in both the long and short run which indicates that Malaysia remains competitive with the Indonesian palm oil in China’s market. Thus, Malaysia should develop plans and strategies to enhance the competitiveness of its palm oil in China. As a recommendation to enhance this study, future studies should adopt a different theory like supply theory or complete market equilibrium theory to confirm the results found in this study. The future researchers are also encouraged to continue this study by employing more up to date data to capture any effect on the presence of structural or behavioural changes.